Diode-pumped SESAM mode-locked Yb:CLNGG laser. (June 2015) - Zhang, Yuangeng; Petrov, Valentin; Griebner, Uwe; Zhang, Xingyu; Yu, Haohai; Zhang, Huaijin; Liu, Junhai
Abstract: Pulses as short as 55 fs are generated at 1051.5 nm with the isotropic disordered crystal Yb:CLNGG under diode pumping using SESAM. The bandwidth of ~23 nm corresponds to almost transform-limited sech 2 -shape pulses. The average power in this case of 1% output coupling is 60 mW at a repetition rate of ~87 MHz. Maximum average output power of 194 mW is achieved with higher output coupling of 5% for which the pulse duration amounts to 115 fs. Highlights: We achieve mode-locking of the disordered Yb:CLNGG crystal with SESAM. We demonstrate the shortest pulses with an isotropic Yb-laser crystal. Maximum average power of 194 mW is obtained at 87 MHz.